HYPNOTEACHING IN HISTORY LESSON - Agus Budianto; Nara Setya Wiratama (IKIP PGRI Bojonegoro, 2017)
Abstract: Hypnoteaching in History Lesson. Historical learning is a science that can’t be separated in educating the younger generation. Through this lesson, teachers in secondary schools can provide the foundation of nationality through important events in the study of the social sciences. Many of the problems that occur in learning history, such as the boring and make sleepy.Everyone must have heard the term hypnosis, hypnotism, or hypnotherapy. Each person must also have a different view or understanding when hearing these terms. Hypnoteaching is one of the learning methods by using the art of communicating to influence learners. Hypnoteaching is a combination of five teaching-learning methods such as quantum learning, accelerate learning, power teaching, neuro-linguistic programming (NLP) and hypnosis.Hypnoteaching can be done using informal hypnosis as well as formal hypnosis. Informal hypnosis is also called indirect hypnosis ie teachers can naturally make the Critical Area learners become no longer critical, through a very persuasive communication pattern. Here's what the teacher can do in Informal hypnosis: (1) get attention; (2) establishing Themes; (3) presenting the structure and regulations; (4) building relationships. If the learners are already comfortable and interested, the next step is to do a formal hypnosis before the lesson begins. Here are the steps that must be done: (1) Induction; (2) Deepening; (3) Deep level test; (4) Suggestion, and; (5) Termination. Keywords: Historical learning, hypnoteaching, hypnosis, hypnotism, hypnotherapy, historyAbstrak: Hipnoteaching dalam Pembelajaran Sejarah. Pelajaran sejarah tidak bisa dihilangkan dalam mendidik para generasi muda. Melalui pembelajaran ini, guru pada sekolah menengah pertama dapat memberikan pondasi rasa nasionalisme melalui peristiwa peristiwa penting dalam pelajaran ilmu pengetahuan social. Masalah yang sering muncul pada pembelajaran ini adalah kebosanan siswa dan mengantuk.Setiap orang pasti pernah mengenal istilah hypnosis, hipnotis, atau hipnoterapi. Setiap orang pasti mempunyai pemahaman yang berbeda ketika mendengar istilah tersebut. Hipnoteaching adalah salaha satu metode mengajar dengan menggunakan senin berkomunikasi untuk mepengaruhi para siswa. Hipnoteaching adalah kombinasi dari lima metode mengajar seperti quantum learning, accelerate learning, power teaching, neuro-linguistic programming (NLP) dan hypnosis.Hypnoteaching dapat diterapkan menggunakan informal hypnosis dan juga informal hypnosis. Informal hypnosis juga disebut sebagai indirect hypnosis, misalnya para guru dapat secara alami membuat area kritis siswa menjadi tidak kritis lgi, melalui pola komunikasi persuasi. Berikut adalah apa yang dapat dilakukan para guru pada informal hypnosis: (1) mendapatkan perhatian; (2) menentukan tema; (3) menyajikan struktur dan aturan; (4) membangun kerjasama. Jika para siswa sudah sudah mencapai posisi nyaman dan tertarik pada kegiatan pembelajaran, langkah selanjutnya yang harus dilakukan adalah : (1) pendahuluan; (2) pendalaman; (30 test tingkat kedalaman; (4) pemberian saran, dan; (5) penutup.Kata kunci: Pembelajaran sejarah, hypnoteaching, hipnosis, hypnotis, hipnoterapi, sejarah.